Group Exhibition-Arrivals Departures, in the frame of the Cyprus Presidency of the European Union - Antoniou, Klitsa (My University, 2026)
Arrivals Departures, in the frame of the Cyprus Presidency of the European Union Installation at Larnaca International Airport Curated by Marina Vryonidou